ANALISIS KEBUTUHAN INFORMASI BAGI PENYUSUNAN RENCANA RESOLUSI KONFLIK DI TAMAN WISATA PERAIRAN (TWP) PULAU PIEH: Analysis of Information Needs for The Preparation of Conflict Resolution Plans in Pieh Island Aquatic Tourism Park (TWP) - Yanti, Delfitri; Darmawan; Sondita, M. Fedi Alfiadi (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2023)
The difference in fishing gear between traditional and modern fishermen triggers conflicts; for the sustainability of the Pieh Island Marine Tourism Park (TWP) area, efforts are needed to prepare an efficient conflict resolution plan by considering relevant data and information. The study aims to identify conflicts in the Pieh Island TWP area, identify data and information needs to develop conflict resolution, analyze the availability of management data in the Pieh Island TWP, and provide recommendations for data and information collection. The research was conducted in the form of field observations and structured interviews through several questions that have been systematically prepared, as well as focus group discussions (FGDs) with the managers of the Work Unit (Satker) who are directly responsible to the Pekanbaru National Marine Protected Area Workshop (LKKPN Pekanbaru) as the Technical Implementation Unit of the TWP National Marine Protected Area Pieh Island. The results of the study are qualitative and quantitative data through descriptive and comparative methods in the form of identification of the type/nature of conflict in TWP, data and information needed in the preparation of conflict resolution, data and information that is already available and that must be collected, the ability of managers to support technically but financially need additional funds, and appropriate conflict resolution as well as some descriptions of recommendations for collecting data and information in TWP. Keywords: information needs, management plan, conflict resolution.